Thomas Hobbes i utjecaj njegove filozofije na suverenitet Bosne i Hercegovine / Thomas hobbes and Influence of his Philosophy on Sovereignty of Bosnia and Herzegovina - Burina, Elmida (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
Thomas Hobbes with his philosophy created materialist as well as very pessimistic philosophical approach which didn‟t find its place in that time, but later on had a continuous influence on western political thoughts. His Leviathan portrays gloomy picture of human beings in their natural state where the life is “nasty, brutal, and short”, and a fear of violent death is the main incentive that drives people to create a state and surrender their natural rights to an absolute authority of sovereign. Primary mission in researching this article has been to raise awareness about existence and comprehension of Hobbes‟s philosophy, his vision of sovereign, along with sway of international Leviathan on Bosnia and Herzegovina. The most important concepts of Hobbes's perception of authority and theory of governing are presented in this article, as well as his arguments for existence of absolute sovereign. In short, there is an analysis of international Leviathan and its influence on sovereignty of Bosnia and Herzegovina. Also, the article presents the current situation of Bosnia and Herzegovina as a prime example of humanity in Hobbes state of nature where the citizens of Bosnia and Herzegovina are experiencing nonviolent war and continue to live in fear of another arms conflict.